A case of ovarian endometrioid adenocarcinoma with yolk sac differentiation and Lynch syndrome - Janhvi Sookram; Brooke Levin; Julieta Barroeta; Kathy Kenley; Pallav Mehta; Lauren S. Krill (Elsevier, 2019)
Ovarian endometrioid adenocarcinoma with yolk sac component has been reported in fewer than twenty cases in the literature. A majority of the diagnoses are described in postmenopausal women without specific reference to germline genetic testing. We describe, to our knowledge, the first case in the English literature of a premenopausal woman that presented with an ovarian endometrioid adenocarcinoma with focal yolk sac component and was subsequently found to have a germline MSH2 mutation confirming a diagnosis of Lynch syndrome. Concurrent diagnosis of ovarian endometrioid adenocarcinoma with yolk sac tumor and Lynch syndrome is an extremely rare finding in a young patient and requires careful follow-up. Genetics evaluation and testing may be reasonable for individuals with this rare or mixed tumor pathology at young age of onset and can have clinical utility in guiding future cancer treatment or surveillance. Keywords: Ovarian endometrioid adenocarcinoma, Yolk sac tumor, Germ cell tumor, Lynch syndrome, Ovarian cancer